2013
DOI: 10.4103/0976-237x.123017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transcutaneous electrical nerve stimulation induced parotid stimulation on salivary flow

Abstract: Aims and Objectives:The main objective of this study was to evaluate the duration of stimulation over the parotid salivary flow following the use of transcutaneous electric nerve stimulation (TENS) in different age groups.Materials and Methods:The study was carried out in three different age groups. Under group A individuals from 21 to 35 years of age, group B 36-50 years and group C above 51 years were considered. In each group 30 subjects were taken of whom 15 were males and 15 were females. The placement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…25 Pattipati S et al in their age and sex matched study on 90 subjects reported increased stimulated salivary rates among individuals aged 36 to 50 years. 19 In present study, which was age and sex matched, it was found that in all the age groups there was statistically significant increase in TENS stimulated saliva compared to unstimulated saliva. The unstimulated and stimulated salivary flow rates in different age groups was not statistically significant.…”
Section: Jcdpsupporting
confidence: 45%
See 1 more Smart Citation
“…25 Pattipati S et al in their age and sex matched study on 90 subjects reported increased stimulated salivary rates among individuals aged 36 to 50 years. 19 In present study, which was age and sex matched, it was found that in all the age groups there was statistically significant increase in TENS stimulated saliva compared to unstimulated saliva. The unstimulated and stimulated salivary flow rates in different age groups was not statistically significant.…”
Section: Jcdpsupporting
confidence: 45%
“…This variation of salivary flow rate was similar to the observation made by Vilas SK et al, 2 and others. 6,[17][18][19][20] In our study, the mean unstimulated salivary flow was 2.60 ± 0.39 ml/5 min. There was 38.46% increase in salivary flow which was statistically significant.…”
Section: Jcdpmentioning
confidence: 92%
“…A study conducted by Hargitai et al ( 9 ) also demonstrated similar results where in 15 out of the 22 subjects had demonstrated increased salivary flow rate. In another study conducted by Pattipati et al ( 10 ) in 2013, showed an increase in salivary flow rate on application of TENS, and more so, this increase in salivary flow was pertinent even one hour after the application of TENS in a select group of individuals.…”
Section: Discussionmentioning
confidence: 89%
“…Pattipati et al ( 34 ) in 2013 used electrostimulation in 90 healthy adults and found that application of TENS over parotid region results in increased salivary flow rate.…”
Section: Applications In Dentistrymentioning
confidence: 99%